Epidemiologists, our patient is society. - Myers DJ (New Solutions: A Journal of Environmental & Occupational Health Policy, 2008)
The common approach utilized in many epidemiologic studies is to measure and compare characteristics and exposures of afflicted and non-afflicted individuals from the same population. The subject of most contemporary chronic disease epidemiology, therefore, is not epidemics per se, nor their causes, but rather epidemics' victims. While these approaches and methods are entirely appropriate for investigating many vitally important health-related questions, it is argued here that epidemics themselves, including those that produce chronic illnesses, should also be the subject of epidemiologic investigations. Epidemics are viewed as phenomena that afflict social entities and should be approached as such.